2022
DOI: 10.31083/j.rcm2302063
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between plasma Neuregulin-1 and cardiac function in patients with ST-elevation myocardial infarction

Abstract: Background: Neuregulin-1 (NRG-1) is a stress-mediated transmembrane growth factor. Reduced myocardial damage and higher NRG-1 levels upon treatment with remote ischemic conditioning (RIC) has been described in rats. However, the role of NRG-1 in patients with acute myocardial infarction (MI) is unknown. Thus, we conducted a post hoc analysis of a randomized controlled trial that tested RIC in patients with MI scheduled for primary percutaneous coronary intervention (PCI). Methods: Blood was drawn from 30 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Although the use of human-recombinant NRG-1 in HF patients significantly increased cardiac output and LVEF, its circulating expression and functional significance as a biomarker in the development of unfavorable post-MI remodeling in patients with STEMI are still unknown [ 217 ]. Research conducted by Haller et al showed that circulating NRG-1 levels in STEMI patients decreased following PCI, with no correlation with other variables, such as total ischemic time, RIC and LV ejection fraction [ 217 , 218 ]. On the other hand, individuals at advanced stages of HF were identified by a large increase in circulating NRG-1 levels but with a reduction in the mRNA expression of ErbB2 and ErB4 [ 218 , 219 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the use of human-recombinant NRG-1 in HF patients significantly increased cardiac output and LVEF, its circulating expression and functional significance as a biomarker in the development of unfavorable post-MI remodeling in patients with STEMI are still unknown [ 217 ]. Research conducted by Haller et al showed that circulating NRG-1 levels in STEMI patients decreased following PCI, with no correlation with other variables, such as total ischemic time, RIC and LV ejection fraction [ 217 , 218 ]. On the other hand, individuals at advanced stages of HF were identified by a large increase in circulating NRG-1 levels but with a reduction in the mRNA expression of ErbB2 and ErB4 [ 218 , 219 ].…”
Section: Resultsmentioning
confidence: 99%
“…Research conducted by Haller et al showed that circulating NRG-1 levels in STEMI patients decreased following PCI, with no correlation with other variables, such as total ischemic time, RIC and LV ejection fraction [ 217 , 218 ]. On the other hand, individuals at advanced stages of HF were identified by a large increase in circulating NRG-1 levels but with a reduction in the mRNA expression of ErbB2 and ErB4 [ 218 , 219 ]. Despite being efficacious in rats, no effect from RIC on plasma NRG-1 levels was found [ 216 , 218 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocardial infarction is characterized by a peak in cardiomyocyte death on the first day ( Whelan et al, 2010 ; Del Re et al, 2019 ). The latest research shows that no association with other variables, NRG-1 plasma levels decreased significantly following PCI/RIC and remained decreased up to 1 month following AMI ( Haller et al, 2022 ). ROS (Reactive oxygen species) generated in cardiac ischemia-reperfusion induce NRG1β/ErbB4 activation ( Kuramochi et al, 2004a ), implying that NRG1β/ErbB4 signaling regulates myocardial injury in an environment of oxidative stress.…”
Section: Nrg1 With Cardiovascular Diseasesmentioning
confidence: 99%
“…Deficiencies in NRG1 are associated with Hirshprung’s disease, leading to poor innervation of the gut (Tang et al, 2012, Garcia-Barcelo et al, 2009), as well as abnormal brain development and mental disorders like bipolar disorder or schizophrenia (Georgieva et al, 2008, Marballi et al, 2012). In contrast, high levels of circulating NRG1 are associated with cardiac disease and morbidity following heart failure (Haller et al, 2022). NRG1 is also involved in modulating the immune response (Alizadeh et al, 2018, Ryzhov et al, 2017), controlling insulin related liver activity (Zhang et al, 2018), cell migration (Jumper et al, 2017) and cell-cell recognition and viability in the central nervous system (Garratt et al, 2000).…”
Section: Introductionmentioning
confidence: 99%